Vacuum-assisted breast biopsy with 7-gauge, 8-gauge, 9-gauge, 10-gauge, and 11-gauge needles: how many specimens are necessary?. (September 2015) - Preibsch, Heike; Baur, Astrid; Wietek, Beate M; Krämer, Bernhard; Staebler, Annette; Claussen, Claus D; Siegmann-Luz, Katja C
Background: Published national and international guidelines and consensus meetings on the use of vacuum-assisted biopsy (VAB) give different recommendations regarding the required numbers of tissue specimens depending on needle size and imaging method. Purpose: To evaluate the weights of specimens obtained with different VAB needles to facilitate the translation of the required number of specimens between different breast biopsy systems and needle sizes, respectively. Material and Methods: Five different VAB systems and seven different needle sizes were used: Mammotome® (11-gauge (G), 8-G), Vacora® (10-G), ATEC Sapphire™ (9-G), 8-G Mammotome® Revolve™, and EnCor Enspire® (10-G, 7-G). We took 24 (11-G) or 20 (7–10-G) tissue cores from a turkey breast phantom. The mean weight of a single tissue core was calculated for each needle size. A matrix, which allows the translation of the required number of tissue cores for different needle sizes, was generated. Results were compared to the true cumulative tissue weights of consecutively harvested tissue cores. Results: The mean tissue weights obtained with the 11-G / 10-G Vacora® / 10-G Enspire® / 9-G / 8-G Original / 8-G Revolve™ / 7-G needles were 0.084 g / 0.142 g / 0.221 g / 0.121 g / 0.192 g / 0.334 g / 0.363 g, respectively. The calculated required numbers of VAB tissue cores for each needle size build the matrix. For example, the minimum calculated number of required cores according to the current German S3 guideline is 20 / 12 / 8 / 14 / 9 / 5 / 5 for needles of 11-G / 10-G Vacora® / 10-G Enspire® / 9-G / 8-G Original / 8-G Revolve™ / 7-G size. These numbers agree with the true cumulative tissue weights. Conclusion: The presented matrix facilitates the translation of the required number of VAB specimens between different needle sizes and thereby eases the implementation of current guidelines and consensus recommendations into clinical practice.